THE COMPOSITIONAL COMPETENCE OF FUTURE TEACHERS AS A PEDAGOGICAL PROBLEM - Erkin Jabborov (American Journals, 2023)
The article explores how a competency approach to the training of future teachers of fine arts can be expressed in the fact that they effectively organize their pedagogical activities in the future. In particular, in composition classes, students can study such information as the preparation of compositions in the direction of Fine Arts, the formation of creative thinking and imagination in them, the implementation of their tasks for the development of artistic vision, taste and memory of vision. In turn, the article also analyzes the components of the compositional competence of the teacher of Fine Arts.
Keywords: Art, Fine Arts, realism, composition, form, content, spirituality, worldview.